Participants in participative processes – who they are and what they think about participation - Kim Pollermann (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
One well established instrument of regional development policy for rural areas is the LEADER-approach, which was started more than 25 years ago. Whereby the representation is often discussed, in evaluations/research projects the participants themselves are less often asked than LAG-managers / Chairpersons. However, different points of view from different types of actors could give insights about the functionality and results of this participative approach. The question for the presentation is: who are the participants (related to gender and age) and what do they think about participation.
Conference: Regional Studies Association Annual Conference 2018, A World of Flows: Labour Mobility, Capital and Knowledge in an Age of Global Reversal and Regional Revival, Lugano, Switzerland
Keywords: R11; 330; Rural Development; LEADER; Participation